2018
DOI: 10.1002/ghg.1755
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ionic liquid mixtures of [NH2e‐mim][BF4] and [bmim][BF4] as absorbents for CO2 capture

Abstract: Although the use of ‘task‐specific’ amine‐functionalized imidazolium‐based ionic liquids (ILs) such as [NH2emim][BF4] and conventional imidazolium‐based ILs [bmim][BF4]), as absorbents for CO2 capture, possesses some unique advantages, they have a number of disadvantages when independently used for CO2 capture. This study examined a series of binary liquid mixtures of [NH2emim][BF4] and [bmim][BF4] for CO2 capture, exploiting the advantages and reducing the disadvantages of each of the components. The CO2 abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Ionic liquids (ILs), which have many unique properties, such as high thermal stability, negligible vapor pressure, high CO 2 capacity, and adjustable structure, are good candidates for CO 2 absorption. Normal ILs, which only have physical interaction with CO 2 , can hardly be used for CO 2 capture from flue gas. Functional IL for CO 2 absorption was first reported by Davis et al, and the CO 2 capacity could reach almost 0.5 mol CO 2 /mol IL at 22 °C and ambient pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs), which have many unique properties, such as high thermal stability, negligible vapor pressure, high CO 2 capacity, and adjustable structure, are good candidates for CO 2 absorption. Normal ILs, which only have physical interaction with CO 2 , can hardly be used for CO 2 capture from flue gas. Functional IL for CO 2 absorption was first reported by Davis et al, and the CO 2 capacity could reach almost 0.5 mol CO 2 /mol IL at 22 °C and ambient pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, molecular docking results suggested the possibility of interactions between ILs and protein that are responsible for the stabilization of β-LG in [Chn]­[Bit], [Chn]­[DHP] and [Chn]­[Ac] . It has also been documented in literature that ILs, when mixed in definite proportions, abrogate the negative effect of one IL by the other IL, giving rise to the advantageous characteristics of the resultant mixture . Inspired by this study and taking forward their previous study, Sindhu et al considered a mixture of ILs to counteract the deleterious action of [Chn]­[I] on β-LG structure.…”
Section: Recent Advances In Exploring Cholinium-based Ionic Liquids F...mentioning
confidence: 70%
“…According to the literature discussed in earlier sections, it has been significantly demonstrated that [Chn]­[DHP] possesses exceptionally high biocompatibility toward proteins (see refs , , , , , , , , , , , , and ). A key factor that influences the stability of proteins in hydrated ILs is the kosmotropicity of the constituent ions, which is directly related to water assembly around proteins.…”
Section: Why Does Cholinium Dihydrogen Phosphate Have Exceptional Abi...mentioning
confidence: 99%
“…Thus, CO 2 absorption experiments were conducted using four kinds of ILs with the same cation but different anions. Many studies have shown that imidazolium‐based ILs demonstrate noticeable CO 2 absorption capacity . The cation [BMIm] + combined with different anions ([AC] − , [BF 4 ] − , [L‐lactate] − , and [PF 6 ] − ) were therefore investigated.…”
Section: Resultsmentioning
confidence: 99%
“…,33 Thus, CO 2 absorption experiments were conducted using four kinds of ILs with the same cation but different anions. Many studies have shown that imidazolium-based ILs demonstrate noticeable CO 2 absorption capacity [34][35][36][37]. The cation[BMIm] …”
mentioning
confidence: 99%